Mathematics Learning Model for Children with Dyscalculia through Special Intervention - Azhari, Budi; Johar, Rahmah; Ramadhani, Evi; Mailizar, Mailizar; Safrina, Khusnul (Jurnal Ilmiah Peuradeun, 2024)
This research aimed to formulate a model of mathematical learning difficulties for children with dyscalculia to help children with dyscalculia overcome mathematics problems at school. This research is important to carry out considering that dyscalculia is a serious problem experienced by many students throughout the world. The SDTA model was built by analogizing the STIR model to non-communicable diseases. In this study, of 1247 students who conducted a series of tests (screening tests), there were 121 students, or 9.7% were initially identified as having dyscalculia. Furthermore, observations were carried out and confirmation was carried out with parents and teachers so that 119 students tested positive for dyscalculia. The research results showed that after intervention through treatment by the teacher, dyscalculia students experienced a very drastic decrease, especially in the material on recognizing and ordering numbers. Likewise, the results of model simulations on multiplication operation material illustrated the decline in students with dyscalculia. Specifically for division operations, the treatment process took relatively longer. Therefore, the simulation results in the SDTA model reflected students who are identified as having dyscalculia, along with planned intervention/ treatment, students could pass through the mathematics learning phase successfully.